KOORDINASI CAMAT DALAM PROSES PEMBANGUNAN DI KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Fatmawati Fatmawati (Katalogis, 2018)
This study aims to identify and explain the coordination of subdistrict heads in the development process in the district of Central Bungku district of Morowali. The location of the research was conducted at the Bungku Tengah District Office of Morowali District. The theory used is coordination according to Hasibuan (2006: 86-87), coordination is divided into two major parts of vertical coordination and horizontal coordination